Formação continuada na escola: reorganização das práticas pedagógicas e perspectivas para o trabalho docente - Calegari, Elis Regina (2015)
This essay will be discussed the process of teacher's continuous training and some ramifications in the education practice. The context this essay was a school of Francisco Beltrão municipal education system, Paraná. The municipal school Juscelino Kubitschek, since 2010, has a singular process of organization this education practices, from now on teacher's continuous training. The focus this essay is in the practices realized in 2013 and 2014, study survey. The general objective of this research is to characterize a continuing training experience of teachers at school, trying to understand the reflection of movements mobilized actions and their consequences in pedagogical practices of teachers. Therefore, in the first chapter will be approached the conceptions and discussions about the teacher's continuous training, as certain analysis are directed about the relations of teacher's continuous training with education practice and teaching work, emphasize, the continuous training centered in school. In the second chapter will be described and analyzed the context of involve the school, the goals to movement of reflection about the education practice and partnership between the school and college. In the third chapter, has some practices that were results of the process of school, specially the "collective moment" as practice of school in the continuous training, the practice of planning for work project achieved for the school, and the forms that the school achieved to work the scholarly collective from now on the practice of self-organization with students. From a qualitative study, we sought to develop as a kind of research the Case Study. The data collection was by means of observations and records as field diaries, semi-structure interviews and analysis of documents. While bibliography discuss, permeate the debates of continuous training situating the categories: continuous training in school, education practice, teaching work, professionalization, partnership between school and college, and planning. In conclusion, the discusses about the continuous training coming have some decades occupying the debate spaces that treat of improvement in quality of education and the connection with the development of education practices. In the context of research, in consideration the indicative of differentiation methodological, performs relation the performance of professionals of school, the form as the collective routing are assumed in individual and collective scope and the external questions that hamper the formation of the pedagogical project with purpose of actions well defined. Therefore, highlight the dimensions of process from now of coordination of actions in the practice of continuous training, of management and collective planning of pedagogical practice from now on the reconstruction of methodology of planning for work project and formation of pedagogical devices that orient the teaching work with the collective of students. Stand out, that has a field comprehensive of potentialities and questions holding and analyzed in continuous training to articulate the dimensions theoretical-practical that involves the all this experience.